1984
DOI: 10.1111/j.1440-6055.1984.tb01904.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF BREED AND COAT COLOUR ON NUMBERS OF THE BUFFALO FLY HAEMATOBIA IRRITANS EXIGUA DE MEIJERE, (DIPTERA, MUSCIDAE) ON BOVINE HOSTS

Abstract: The numbers of buffalo flies on individual animals in a herd containing 4 water buffalo, 4 Brahman, 4 Belmont Red (50% Zebu blood) and 3 Hereford Shorthorn steers were counted on 1 I occasions during the 1976/7 wet summer season at Rockhampton, ( 2 3 3 , 150'W). There were consistent differences in the numbers of buffalo flies found on individual animals within a herd. On average there were about 5 times as many flies on the most heavily infested individual as on the least heavily infested. These differences p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The zebu breed (Doube 1984, Steelman et al 1997) may explain the relatively low number of flies/cow observed in this study (maximum of 84). Low infestations have been found in other parts of the Brazilian mid-west, where zebu cattle have been raised extensively.…”
Section: Discussionmentioning
confidence: 78%
“…The zebu breed (Doube 1984, Steelman et al 1997) may explain the relatively low number of flies/cow observed in this study (maximum of 84). Low infestations have been found in other parts of the Brazilian mid-west, where zebu cattle have been raised extensively.…”
Section: Discussionmentioning
confidence: 78%
“…1964 ; Morgan, 1964; Schreiber & Campbell, 1986) but not others ( Tugwell et al . 1969 ; Doube, 1984; Ernst & Krasfur, 1984). Controversial results have also been obtained for the relationship between the proportion of B. indicus genes and H. irritans infestations ( Tugwell et al .…”
Section: Discussionmentioning
confidence: 99%
“…(1969) stated that cattle carried a decreasing number of flies as the percent of Brahma, Bos indicus Linnaeus, genes increased. Doube (1984) and Brethour et al . (1987) found evidence to support this finding and Steelman et al .…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, certain phenotypes within breeds are more resistant to horn flies. Several studies have shown the existence of low‐carrier phenotypes, manifested by individuals with low horn fly levels in the field (Doube, 1984; Schreiber & Campbell, 1986; Pruett et al , 2003; Jensen et al , 2004), and this trait appears to have good heritability (Brown et al , 1992). Another Diptera species that bites animals, tsetse flies (Diptera: Glossinidae), also displays intraspecific host preference (Torr et al , 2001).…”
Section: Alternative Control Strategiesmentioning
confidence: 99%